The Determinants of Capital Structure: Evidence from Chinese-listed companies - WANG, YUAN (2019)
This dissertation studies the determinants of capital structure of the Chinese-listed companies by utilizing a balanced panel data comprising 154 Chinese-listed companies from 2009 to 2018. Specifically, the potential determinants of Chinese-listed companies’ capital structure that will be tested in this paper are profitability, firm size, growth opportunities, tangibility, liquidity, non-debt tax shields, effective tax rate, state ownership, management ownership, time effects and economic downturns. To achieve this objective, we first review the capital structure theories, especially the trade-off theory and the pecking order theory. Based on the various theories, we set the testable hypotheses for each potential determinant. Afterwards, the panel data estimators-Within Group estimator (Fixed-Effects model) including time dummy variables, is used to empirically test the determinants. The empirical results have indicated that Chinese-listed companies’ capital structure are basically consistent with the literature from developed and developing countries, and highlight the particularity of China's financial market. First, we found mixed evidence to support the different theories, but appear to be a greater validity of the pecking order theory for Chinese-listed companies. Long-term leverage is positively affected by tangibility, which provides evidence in support of trade-off theory. In addition, profitability is negatively related to leverage, indicating that pecking order theory is more relevant. This mixed evidence reflects China's peculiarities institutional environment. Second, ownership structure is found to have a significant impact on capital structure. In particular, companies with a higher level of state ownership will have lower short-term leverage, while higher manager ownership will result in more short-term debt. Third, it was found that Chinese companies' borrowing demand will change over time, which is related to changes in the broader market economic cycle. Specifically, economic downturns are negatively related to leverage, in terms of total leverage and short-term leverage, which shows that Chinese companies are bound to China’s specialised planned-economy system.